Effect of different building envelope materials on thermal comfort and air-conditioning energy savings: A case study in Basra city, Iraq - Homod R.Z.; Almusaed A.; Almssad A.; Jaafar M.K.; Goodarzi M.; Sahari K.S.M. (Elsevier Ltd, 2023)
Air conditioning; Autoclaved aerated concrete; Energy utilization; Heating; HVAC; MATLAB; Solar buildings; Thermal comfort; Air-conditioning energy savings; Building envelopes; Empirical correlations; Energy saving potential; Hybrid calculations; MATLAB/Simulink environment; Residential load factors; Vernacular buildings; Energy efficiency